2019
DOI: 10.1016/j.vacuum.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur corrosion effect on the electrical performance of silver films elaborated by physical vapor deposition

Abstract: Electrical properties of Ag films elaborated by Physical Vapor Deposition (PVD) process has been studied before and after corrosion exposure.We have shown that the minimum thickness of silver to resist to sulphurization atmosphere is one micron with an adherent coating. After a sulfurization time of 600 min, an electrical resistivity increase of only 10 % is obtained for a film with 2 microns in thickness. This value is about 20 % higher than the electrical resistivity of pure silver bulk material.For industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As shown in Figure b, the XPS survey spectrum confirmed the existence of Ag, O, and S on the surface of RM-FTCE after the accelerated test. Previous studies have revealed that silver sulfide is the main corrosion product, causing electrical failures of silver film . The high-resolution XPS spectrum of S 2p, as shown in Figure c, indicates that both the in-plane RM-FTCE and the out-of-plane RM-FTCE were all corroded during the accelerated test.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in Figure b, the XPS survey spectrum confirmed the existence of Ag, O, and S on the surface of RM-FTCE after the accelerated test. Previous studies have revealed that silver sulfide is the main corrosion product, causing electrical failures of silver film . The high-resolution XPS spectrum of S 2p, as shown in Figure c, indicates that both the in-plane RM-FTCE and the out-of-plane RM-FTCE were all corroded during the accelerated test.…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies have revealed that silver sulfide is the main corrosion product, causing electrical failures of silver film. 49 The high-resolution XPS spectrum of S 2p, as shown in Figure 4c, indicates that both the in-plane RM-FTCE and the out-of-plane RM-FTCE were all corroded during the accelerated test. However, the sulfurization degree of the in-plane RM-FTCE is rather weaker, comparing with that of the out-of-plane RM-FTCE.…”
Section: Resultsmentioning
confidence: 95%
“…To fabricate biointerfaces containing silver, CVD methods commonly reduce a silver precursor to form nanometer-scale silver layers/composites/nanoparticles, whereas PVD typically involves transfer and deposition of metal silver. , Coatings of pure silver have been employed for a range of antimicrobial applications. Micron-thick silver PVD coatings on limb prosthetics have been utilized to prevent infection until skin cells took over to fill that role .…”
Section: Antimicrobial Biointerfacesmentioning
confidence: 99%
“…Among the physical methods used to produce MNPs films, the Physical Vapor Deposition (PVD) approach is one of the best known; it has the advantage of not requiring solvents, but it uses heavy machinery and involves significant energy consumption. 10 Ghidelli et al used an ex situ synthesis of gold nanoparticles by pulsed laser deposition (PLD) to develop nanostructured Au films with tailored optical properties in a pure Ar background gas. 11 However, this method requires severe deposition conditions such as high background pressures, high number of laser shots (500 shots), and high temperature of post-deposition annealing treatments up to 650 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the physical methods used to produce MNPs films, the Physical Vapor Deposition (PVD) approach is one of the best known; it has the advantage of not requiring solvents, but it uses heavy machinery and involves significant energy consumption [10]. Ghidelli et al used an ex-situ synthesis of gold nanoparticles by pulsed laser deposition (PLD) to develop nanostructured Au films with tailored optical properties in a pure Ar background gas [11].…”
mentioning
confidence: 99%